North-facing elevation of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the north-facing elevation of the Chaunsath Yogini Temple. At the centre of a high plinth, there is a single shrine temple of which only the garbhagriha (sanctum sanctorum) has partially survived. Originally, the temple must have had a garbhagriha, an antarala (vestibule and antechamber) and a mandapa (pillared hall) with attached mukhamandapas (front porch). There are two varieties of sandstone used in the construction of this temple.